The National Assessment of Mathematics in High Schools in Italy with Slovene as the Language of Instruction - Doz, Daniel (Revija za elementarno izobraževanje, 2019)
In the following paper, we analyzed the question types in the INVALSI national mathematics assessments in Italian high schools with Slovene as the language of instruction. Through a statistical analysis, we found that closed-type questions were more frequent than open-type questions. A greater presence of closed-type questions could lead to the issue of guessing and cheating. Moreover, a greater quantity of closed-type questions could lead to a partial evaluation of knowledge, since procedures and other mathematical competences are not considered. In our research, we also considered the topics of the questions that were presented in national assessments.
Keywords: mathematics; Slovene education in Italy; national examinations; testing